2015
DOI: 10.1149/2.0241506jes
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of the Ionic Liquid Pyr14TFSI with Superoxide Radicals Generated from KO2or by Contact of O2with Li7Ti5O12

Abstract: Ionic liquids are attractive candidates as electrolyte solvents for Li-O 2 cells, primarily due to their low volatility, high anodic stability, and low flammability. Specifically, the ionic liquid 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide (Pyr 14 TFSI) has attracted considerable attention thanks to its electrochemical and chemical stability. In this work, we demonstrate via our recently developed UV-Vis screening method that Pyr 14 TFSI unfortunately reacts with the superoxide radical (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 59 publications
4
23
0
2
Order By: Relevance
“…[11] In those experiments,H 2 was detected as amajor gas phase byproduct during discharge,pointing to a b-H elimination mechanism by acid-base chemistry.T wo recent studies by the Gasteiger group provided strong evidence to support the decomposition pathways of PYR 14 TFSI (1-butyl-1-methylpyrrolidinium bis-(trifluoromethanesulfonyl)imide) following the Hofmann elimination mechanism. [47,48] As as oft acid, PYR cation interacts favorably with superoxide,w hich is as oft base, according to the half-soft acid-base (HSAB) theory. [49] This interaction helps stabilize superoxide in the electrolyte, promoting OER reactions following ao ne-electron process.…”
Section: The Role Of Oxygen Species In Acid-base Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] In those experiments,H 2 was detected as amajor gas phase byproduct during discharge,pointing to a b-H elimination mechanism by acid-base chemistry.T wo recent studies by the Gasteiger group provided strong evidence to support the decomposition pathways of PYR 14 TFSI (1-butyl-1-methylpyrrolidinium bis-(trifluoromethanesulfonyl)imide) following the Hofmann elimination mechanism. [47,48] As as oft acid, PYR cation interacts favorably with superoxide,w hich is as oft base, according to the half-soft acid-base (HSAB) theory. [49] This interaction helps stabilize superoxide in the electrolyte, promoting OER reactions following ao ne-electron process.…”
Section: The Role Of Oxygen Species In Acid-base Reactionsmentioning
confidence: 99%
“…See Section 2.5 for discussions of the SEI formation and functionality. [31,35] --Ether/polyether -O ,P [20,42,44,51] -O [43] DMSO B, [32] N [30] B, [32] N, [30] P [46] R [19] -Ionic liquid -B [47,48] R [47] -Amide -N [39,40] R [55] -Notes:N:nucleophilic attack;B:acid-base reaction;O:auto-oxidation; P: proton-mediated process;R:r eduction by Li.…”
Section: Corrosion Of Lithium By the Electrolytesmentioning
confidence: 99%
“…In diesen Versuchen wurde H 2 als Hauptnebenprodukt in der Gasphase während des Entladens nachgewiesen, was auf einen Mechanismus der β‐H‐Eliminierung über Säure‐Base‐Reaktionen hindeutet. Zwei neuere Studien der Gruppe von Gasteiger erbrachten den eindeutigen Nachweis der Zersetzungswege von 1‐Butyl‐1‐methylpyrrolidiniumbis(trifluormethansulfonyl)imid (PYR 14 TFSI) nach dem Mechanismus der Hofmann‐Eliminierung . Als weiche Säure wechselwirkt das PYR‐Kation gut mit Superoxid, das eine weiche Base ist – gemäß dem Konzept der harten und weichen Säuren und Basen, HSAB‐Konzept (HSAB, Hard and Soft Acids and Bases) .…”
Section: Wege Der Elektrolytzersetzungunclassified
“…Infolgedessen werden nur geringe Überspannungen beim Laden gemessen . Die relativ hohe Konzentration an Superoxid in PYRTFSI fördert jedoch auch die β‐H‐Eliminierung am PYR‐Kation durch das Superoxid, was zur Zersetzung des Elektrolyten führt …”
Section: Wege Der Elektrolytzersetzungunclassified
“…Several studies have reported the long-term stability of O2 − with ILs (AlNashef et al, 2010;Hayyan et al, 2012d;Hayyan et al, 2012f) and other electrolytes, such as glyme (Schwenke et al, 2013). Recently, Schwenke et al (2015) monitored O2 − with 1-butyl-1-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide for 18 h.…”
Section: Introductionmentioning
confidence: 99%